2021
DOI: 10.1080/13876988.2021.1880871
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Motivations for Including Enforcement in US COVID-19 State Executive Orders

Abstract: The United States' response to COVID-19 has been predominantly led by state governments. To understand if, why, and how state governments include enforcement language in their executive order response, this article conducts an analysis based on 1,357 coded executive orders. It is found that decisions to include enforcement language are influenced by a governor's political circumstances and perceived risks associated with the crisis. This paper offers insight into how these findings are important for future res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…Specifically, arrests for these violations were higher in areas with greater levels of poverty and minority populations, suggesting trends in differential enforcement. Alternatively, some states had clear enforcement guidelines but were up against police resistance to such enforcement, which again may shape public relationships between law enforcement and the perceived legitimacy of law enforcement, when the police themselves are not following or enforcing the guidelines (Curley et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, arrests for these violations were higher in areas with greater levels of poverty and minority populations, suggesting trends in differential enforcement. Alternatively, some states had clear enforcement guidelines but were up against police resistance to such enforcement, which again may shape public relationships between law enforcement and the perceived legitimacy of law enforcement, when the police themselves are not following or enforcing the guidelines (Curley et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Policy signals produce shared understandings, norms, and identities. In the case of COVID-19, the emergence of state COVID-19 policies may have signaled the public health risk of the pandemic (Curley et al, 2021), highlighting its' seriousness and legitimizing voluntary action.…”
Section: Policy Signalingmentioning
confidence: 99%
“…Some other research showed that leader gender does not influence political communication. For example, one study found no significant difference between male and female governors' enforcement language in executive order responses during COVID‐19 (Curley et al, 2021 ). Another cross‐national study found that leader gender did not influence the timing of implementing COVID‐19 containment policies such as stay‐at‐home orders and schools closure (Aldrich & Lotito, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%